2019
DOI: 10.1111/add.14810
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early nausea on varenicline adherence and smoking cessation

Abstract: Background and aims Varenicline effectiveness may be related to the level of adherence, which might be reduced by adverse effects such as nausea. The aim of the study was to test a possible effect of nausea on smoking cessation outcomes mediated by adherence. Design Mediation path analysis. Setting Multiple sites within Canada and the United States. Participants Treatment‐seeking smokers receiving varenicline from two smoking cessation clinical trials: Quit2Live (NCT01836276; n = 449) and Pharmacogenetics of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…some participants reported stopping medication because of AEs), or contributed to loss to follow‐up or the higher withdrawal rate seen in the varenicline group. Early nausea during varenicline treatment may reduce adherence and be associated with lower likelihood of smoking cessation [ 33 ], so should be anticipated and managed in people taking cytisine or varenicline. The lower incidence of nausea in the cytisine group is probably due to cystine's slower potency at 5‐HT 3 receptors [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…some participants reported stopping medication because of AEs), or contributed to loss to follow‐up or the higher withdrawal rate seen in the varenicline group. Early nausea during varenicline treatment may reduce adherence and be associated with lower likelihood of smoking cessation [ 33 ], so should be anticipated and managed in people taking cytisine or varenicline. The lower incidence of nausea in the cytisine group is probably due to cystine's slower potency at 5‐HT 3 receptors [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of nausea rates in 2 smoking cessation clinical trials conducted at multiple sites in the U.S. and Canada found that early nausea was indirectly associated with lower cessation rates at multiple timepoints as a result of reduced varenicline adherence (ORs ranging from 0.92–0.94; 95% CI between 0.83–0.99). 16 A prior analysis of 6 varenicline clinical trials found that nausea was the most common AE, occurring in 28.1% of participants. 17 In contrast, in the ORCA-1 study described here, fewer than 10% of participants reported nausea as an AE ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were randomized in a 2:2:1 ratio to receive cytisinicline 1.5 mg, cytisinicline 3 mg, or placebo (Supplemental Figure 1). After randomization, each participant was required to attend 11 clinic visits [ Day 2,3,6,12,16,20 during treatment, at End of Treatment (EOT: Day 27 ± 2), and then weekly post-treatment at Week 5,6,7,8]. All participants received approximately 10 minutes of smoking cessation counseling at each clinic visit provided by experienced counselors.…”
Section: Methodsmentioning
confidence: 99%
“…Even with dose titration, ~28% of smokers receiving varenicline treatment in clinical trial settings report nausea (3), and nausea is a commonly cited reason for discontinuation of treatment (5). We have shown that in vareniclinetreated smokers, nausea is indirectly associated with lower quit rates, in a relationship that is mediated by reduced varenicline adherence (6). A greater understanding of the factors that increase the risk for varenicline-associated nausea will enable improved treatment approaches that increase medication adherence and promote cessation.…”
Section: Introductionmentioning
confidence: 87%
“…a week after the target quit date). Varenicline levels were measured in saliva samples using LC-MS/MS (details available elsewhere (6,18)). The sensitivity analyses were conducted in SNPTEST version 2.5.2 and the "method -expected" option was specified to control for genotype uncertainty.…”
Section: Sensitivity Analysesmentioning
confidence: 99%